Proximal to Distal Exostectomy for the Treatment of Insertional Achilles Tendinopathy. Issue 4 (August 2018) - McBeth, Zachary L.; Galvin, Joseph W.; Robbins, Justin
When insertional Achilles tendinopathy is addressed surgically via a central-Achilles splitting approach, the calcaneal osteotomy has classically been performed from distal to proximal. We describe a simple proximal to distal technique that allows optimal resection of both the calcaneal exostosis and Achilles enthesophyte, minimizes risk to the soft tissues and skin, provides a bony attachment surface parallel to the axis of the Achilles tendon, and avoids the risk of osteotomy extension into the subtalar joint. Levels of Evidence: Level V: Technique tip